A quadriceps femoris motor pattern for efficient cycling - Hering, G. O.; Bertschinger, R.; Stepan, J. (PLOS ONE, 2023)
In cycling, propulsion is generated by the muscles of the lower limbs and hips. After the first reports of pedal/crank force measurements in the late 1960s, it has been assumed that highly trained athletes have better power transfer to the pedals than recreational cyclists. However, motor patterns indicating higher levels of performance are unknown. To compare leg muscle activation between trained (3.5-4.2 W/kgbw) and highly trained (4.3-5.1 W/kgbw) athletes we applied electromyography, lactate, and bi-pedal/crank force measurements during a maximal power test, an individual lactate threshold test and a constant power test. We show that specific activation patterns of the rectus femoris (RF) and vastus lateralis (VL) impact on individual performance during high-intensity cycling. In highly trained cyclists, we found a strong activation of the RF during hip flexion. This results in reduced negative force in the fourth quadrant of the pedal cycle. Furthermore, we discovered that pre-activation of the RF during hip flexion reduces force loss at the top dead center (TDC) and can improve force development during subsequent leg extension. Finally, we found that a higher performance level is associated with earlier and more intense coactivation of the RF and VL. This quadriceps femoris recruitment pattern improves force transmission and maintains propulsion at the TDC of the pedal cycle. Our results demonstrate neuromuscular adaptations in cycling that can be utilized to optimize training interventions in sports and rehabilitation.